The Impact of Public Financing, Economic Growth, and Corruption on Immunization Performance: Evidence from 37 Sub-Saharan African Countries - Komi Ahawo, Alain; Essoh, Tene-Alima; Collins Adeyanju, Gbadebo; Aplogan, Aristide; Koumavi Ekouevi, Didier (International Journal of Global Health, 2025)
Background In sub-Saharan Africa, where many countries continue to experience high burdens of vaccine-preventable diseases, increasing immunization access have been a priority for the governments and international organizations such as Gavi, the Vaccine Alliance. Over 40 Gavi-supported African countries have been impacted, with 364 million children reached and over US$5.7 billion disbursed, averting over 8.9 million child deaths. Despite this progress, the African region has struggled with immunization coverage due to various factors. Nevertheless, some African countries are transitioning out of Gavi support due to economic growth. However, many require strong political will to increase their expenditure on immunization. This study therefore aims to understand the factors influencing immunization performance and its relationship to public expenditure. Methods Data on 37 Gavi-eligible sub-Saharan African countries between 2006 and 2019 was obtained from the World Bank’s World Development Indicators, the WHO and UNICEF Joint Reporting Form and the Transparency International’s Corruption Perception Index. Descriptive immunization and health expenditure were analyzed using a panel regression of variables. DPT3 was used as an indicator of immunization uptake. The indicator for public expenditure on immunization per child was based on government spending on immunization divided by the number of children in the birth cohort. Results The average gross national income increased from US$639 to US$1,192 per capita, while government spending on immunization increased from US$1.7 to about US$4.5 per child. The findings show that there is a correlation between improved immunization financing, increased gross national income, reduced corruption, and improved immunization coverage. However, performance declines beyond a certain threshold when gross national income per capita increases. In addition, an English-speaking country effect was observed. Conclusions While improved immunization financing increases immunization coverage and constitutes an advocacy talking point, there is a need to understand why an increase in gross national income per capita does not translate into an improved immunization coverage. Key highlights Increasing national spending on immunization drives up the uptake of childhood vaccines. There is a threshold beyond which immunization coverage falls despite increased GNI. Controlling corruption increases immunization coverage tendency. French- and English-speaking countries’ immunization coverage differs. Immunization and health system financing have separate outcomes.
Keywords: Immunization Performance; Public Financing; Economic Growth; Corruption; Sub-Saharan Africa